Fully understanding the efficacy profile of the COVID-19 vaccination and its associated factors in multiple real-world settings - Panahi, Yunes; Einollahi, Behzad; Beiraghdar, Fatemeh; Darvishi, Mohammad; Fathi, Saeid; Javanbakht, Mohammad; Shafiee, Sepehr; Akhavan-Sigari, Reza (Frontiers in Immunology, 2022)
Regarding the association of prior SARS-CoV-2 infection with higher antibody responses, a growing body of evidence suggests that boosting of infection-acquired immunity for both the first and second doses of the BNT162b2 and ChAdOx1 nCoV-19 vaccines was associated with high and durable protection. Regarding likelihood of vaccine escape variants evolving, ongoing examination of the protection conferred against an evolving virus (new variant) by an extended schedule can be crucial.